The Val66 and Met66 Alleles-Specific Expression of BDNF in Human Muscle and Their Metabolic Responsivity - de Assis, Gilmara Gomes; Hoffman, Jay R.; Bojakowski, Jacek; Murawska-Ciałowicz, Eugenia; Cięszczyk, Paweł; Gasanov, Eugene V. (Frontiers in Molecular Neuroscience, 2021)
Brain-derived neurotrophic factor (BDNF) plays an essential role in nervous system formation and functioning, including metabolism. Present only in humans, the ‘Val66Met’ polymorphism of BDNF gene (BDNF) is suggested to have a negative influence on the etiology of neurological diseases. However, this polymorphism has only been addressed, at the molecular level, in non- human models. Knowledge about Val66- and Met66-variant differences to date has been achieved at the protein level using either cell culture or animal models. Thus, the purpose of our study was to analyze the impact of the Val66Met polymorphism on BDNF expression in healthy humans and compare the allele-specific responses to metabolic stress. Muscle biopsies from 13 male recreational athletes (34±9 y, 1.80±0.08 m, 76.4±10.5 kg) were obtained before and immediately following a VO2max test. Allele-specific BDNF mRNA concentrations were quantified by droplet digital PCR (ddPCR) in heterozygous and homozygous subjects. Results indicated that BDNF expression levels were influenced by the genotype according to the presence of the polymorphism. BDNF expression from the Met66-coding alleles, in heterozygotes, were 1.3-fold lower than the Val66-coding alleles. Total BDNF mRNA levels in these heterozygotes remained below the whole sample’s average. A partial dominance was detected for the Val66-coding variant on the Met66-coding’s. BDNF expression levels decreased by an average of 1.8-fold on average following the VO2max test, independent of the individual’s genotype. The results of this study indicate that metabolic stress downregulates BDNF expression but not plasma BDNF concentrations. No correlation between expression level and plasma BDNF concentrations were found.